PERILAKU ASERTIF DALAM MENOLAK AJAKAN PENYALAHGUNAAN NARKOBA DITINJAU DARI GENDER - Astuti, Dwi (Jurnal Empati Bimbingan dan Konseling, 2021)
This study aims to describe the assertive behavior of male and female students' assertive behavior to reject the invitation to drugs abuse. The population used was the tenth and eleventh graders of Vocational School Student of Bandar Pacitan in the academic year of 2020/2021 with a population of 212 students and samples were taken using saturated sampling techniques. The data collection method used an assertive behavior questionnaire. The validity of the instrument used the product moment formula and its reliability used the Alpha formula. Data analysis used percentage descriptive and quantitative analysis using statistical formula t-test or independent samples t-test. The validity, reliability, and data analysis were assisted by the SPSS 21 for Windows program. The results of the analysis showed that assertive behavior to refuse the invitation to drug abuse by female students was higher with an average of 80.17% compared to male students who obtained an average of 72.68%. The conclusion of this study was that there was a significant difference in the assertive behavior of male and female students to reject the invitation to drugs abuse.Â Keywords: Assertive behavior; Drugs and Youth.